JUNIOR HIGH SCHOOL STUDENTS’ CREATIVITY IN SOLVING HOTS QUESTIONS BASED ON LEARNING CONCENTRATION - Astridtia Putri Junita Sari; Janet Trineke Manoy (Program Studi S1 Matematika UNESA, 2022)
Creativity is a product of someone's creative thinking. HOTS questions are questions that are used to measure students' higher order thinking skills. Learning concentration is a process of focusing the mind on learning to the exclusion of other things outside of learning. This study aims to analyze the creativity of junior high school students in solving mathematics HOTS questions based on learning concentration. This type of research includes qualitative descriptive research, with 6 research subjects as representatives of the very high, high, and moderate learning concentration groups. The instruments used in this study were a learning concentration questionnaire, mathematics HOTS questions, and interview guidelines. The data from the learning concentration questionnaire were analyzed using a Likert Scale, the data from the creative thinking ability test were analyzed based on the components of creative thinking. The data from the test and interviews were analyzed using the method of Miles, Huberman, and Sadana. The results showed that students with very high levels of learning concentration were classified as very creative, not all students with high levels of learning concentration could achieve the components of fluency and flexibility. Meanwhile, students with moderate levels of learning concentration were classified as less creative.